(untitled) - Thacker, Claire (Cambridge, U.K., 2004)
English in Mind is a four - level course for teenager which combines engaging content with a strong focus on grammar and vocabulary. It takes students from beginner to intermediate level and is ideal for mixed - ability classes.
Keywords: English language,English language,Ngôn ngữ Anh,Ngôn ngữ Anh; Study and teaching,Học và dạy